2017
DOI: 10.9745/ghsp-d-16-00205
|View full text |Cite
|
Sign up to set email alerts
|

Availability and Quality of Family Planning Services in the Democratic Republic of the Congo: High Potential for Improvement

Abstract: A few facilities provided good access to and quality of family planning services, particularly urban, private, and higher-level facilities. Yet only one-third offered family planning services at all, and only 20% of these facilities met a basic measure of quality. Condoms, oral contraceptives, and injectables were most available, whereas long-acting, permanent methods, and emergency contraception were least available. Responding to the DRC's high unmet need for family planning calls for substantial expansion o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
40
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(46 citation statements)
references
References 21 publications
2
40
0
Order By: Relevance
“…According to a study conducted in 2014, only 33% of health facilities in the DRC have family planning available, and of these only 20% provide quality services according to criteria specific to the study. 7 …”
Section: Introductionmentioning
confidence: 99%
“…According to a study conducted in 2014, only 33% of health facilities in the DRC have family planning available, and of these only 20% provide quality services according to criteria specific to the study. 7 …”
Section: Introductionmentioning
confidence: 99%
“…In the Democratic Republic of the Congo (DRC), the national modern contraceptive prevalence rate among married women of reproductive age is extremely low (7.8%), while unmet need is high (27.7%) and only one-third of facilities offer any family planning services. 26 , 27 The Ministry of Health (MOH) is working to address these issues by making a national commitment as part of the Family Planning 2020 (FP2020) global movement and establishing a country action plan to increase PPFP access. 28 – 31 EngenderHealth's Expand Family Planning Project (ExpandFP) (2013–2020) is one of many efforts funded by the Bill & Melinda Gates Foundation and other donors to support the DRC MOH to move toward their FP2020 and PPFP goals.…”
Section: Introductionmentioning
confidence: 99%
“…As a result, several social and economic consequences arise at the household level: exclusion from health care, indebtedness and high use of the informal sector [15,39,48].It is true that the presence of quali ed personnel during all deliveries is considered to be one of the most important interventions for safer births because it reduces maternal deaths and increases successful delivery of infants [41,[49][50][51]. On the other hand, as this study and several other studies have demonstrated, in poor countries, women and families who must pay out-of-pocket for the costs of care suffer in terms of their physical, mental and social states, and these distressing repercussions are linked to the unaffordable cost of the care they receive.This issue also raises questions regarding staff motivation, patient-centered care, the renewal of equipment, the supply of drugs to maintain quality, the availability of care and the improvement of conditions in the health infrastructure [52][53][54]. These issues are all the more serious because they occur at the level of state structures that normally should be supported by the government but are not su ciently supported because of the slow disbursement of budgetary allocations, which already do not meet the requirements of the Abuja Agreements [17,55,56].All in all, in an environment where seven out of ten households are poor, we believe that the Congolese State should, failing to introduce free healthcare, follow the example of several other countries [15,30,40,57,58]: create an effective and sustainable healthcare subsidy policy; favor and promote the establishment of cost-sharing and/or nancial risk systems that focus on the poorest households; and improve the quality of care and ensure that care management is based on community participation, especially that of male sexual partners, who are equally involved in conception [36,38,59].…”
Section: Discussionmentioning
confidence: 99%